Congenital Heart Disease Diagnosed Prenatally in Cienfuegos. 10 Year Study - Nancy González Vales; Rossana Isabel Jiménez Arias; María Antonia Ocaña; Nicolás Ramón Cruz Pérez; Julio César Martínez Santana; Jan Oneil González Ramos (Universidad de las Ciencias Médicas de Cienfuegos, 2019)
Foundation: congenital heart disease is any heart defect present at birth and occurs as a result of alterations in organogenesis. They constitute the severe structural malformation of greater prevalence and greater impact on neonatal morbidity and mortality. Objective: to determine the characteristics of congenital heart diseases diagnosed prenatally in the province of Cienfuegos in a 10-year study. Method: a descriptive, retrospective cross-sectional study was carried out. The universe consisted of 93 pregnant women with a prenatal diagnosis of congenital heart disease. The variables analyzed were: association of maternal age with the appearance of heart disease, gestational age at diagnosis, year of prenatal diagnosis and its relationship with the evolution of pregnancy, pathological history, risk factors, types of congenital heart disease and its relationship with the pregnancy continuity, results of pathological anatomy of the fetuses, relationship between the diagnosis of congenital heart diseases and the results of pathological anatomy with the pregnancy continuity, behavior of the prenatal diagnosis and the possible annual increase in the mortality rate. Results: the most frequent maternal age was between 19-35 years, which were between 13 and 26 gestational weeks. A 78,4 % of couples decided pregnancy interruption. The most prenatally diagnosed congenital heart disease was inter-ventricular communication followed by hypoplasia of the left cavities, which was the most frequent anatomic-pathological diagnosis. Conclusions: congenital heart disease currently continues to be one of the main causes of death in the first year of life.